2016
DOI: 10.1155/2016/5170419
|View full text |Cite
|
Sign up to set email alerts
|

Significance of “Not Detected but Amplified” Results by Real-Time PCR Method for HPV DNA Detection

Abstract: Human papillomavirus (HPV) infection is an important etiologic factor in cervical carcinogenesis. Various HPV DNA detection methods have been evaluated for clinicopathological level. For the specimens with normal cytological finding, discrepancies among the detection methods were frequently found and adequate interpretation can be difficult. 6,322 clinical specimens were submitted and evaluated for real-time PCR and Hybrid Capture 2 (HC2). 573 positive or “Not Detected but Amplified” (NDBA) specimens by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Importantly, the not detected but amplified (NDBA) phenomenon for the Abbott RealTime assay, i.e., the event in which the assay reports samples to be negative despite showing an amplification curve with a C q value higher than the manufacturer’s positivity cutoff (32.00), as described by earlier research of Kim and colleagues ( 21 ), also occurred frequently within our sample selection. Kim and colleagues ( 21 ) suggested that samples NDBA should be regarded as equivocal, not negative, considering that they could be a sign of a low-copy presence of hrHPV. Consequently, a comparison between the four HPV assays was also performed using a less stringent C q cutoff range for positivity on the Abbott RealTime assay, being 32.00 to 36.00.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Importantly, the not detected but amplified (NDBA) phenomenon for the Abbott RealTime assay, i.e., the event in which the assay reports samples to be negative despite showing an amplification curve with a C q value higher than the manufacturer’s positivity cutoff (32.00), as described by earlier research of Kim and colleagues ( 21 ), also occurred frequently within our sample selection. Kim and colleagues ( 21 ) suggested that samples NDBA should be regarded as equivocal, not negative, considering that they could be a sign of a low-copy presence of hrHPV. Consequently, a comparison between the four HPV assays was also performed using a less stringent C q cutoff range for positivity on the Abbott RealTime assay, being 32.00 to 36.00.…”
Section: Discussionmentioning
confidence: 75%
“…For all HPV assays, concordance results were analyzed based on the manufacturer’s recommended C q cutoff for positivity. However, as described in earlier research ( 21 ), the Abbott RealTime assay often reports samples as HPV negative, while showing an amplification curve with a C q value above the manufacturer-defined cutoff for positivity (<32.00) (NDBA [not detected but amplified]). Therefore, in the current study, concordance and agreement between the different HPV assays was determined both by using the Abbott RealTime manufacturer’s recommended C q cutoff for positivity (<32.00) and by using a less stringent C q range for positivity on NDBA samples (32.00 to 36.00).…”
Section: Methodsmentioning
confidence: 98%